2019
DOI: 10.1016/j.jaci.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

IL-17–producing ST2+ group 2 innate lymphoid cells play a pathogenic role in lung inflammation

Abstract: During lung inflammation, IL-33 and leukotrienes synergistically induce ILC2s. ILC2s are a highly pathogenic and unexpected source for IL-17 in lung inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 60 publications
8
97
1
1
Order By: Relevance
“…In addition, LTC4 and LTD4 have a synergistic effect on ILC2s in combination with IL‐33. It has also been recently shown that a combination of IL‐33 with LTC4 or LTD4 can induce IL‐17 expression in ILC2s . Mechanistically, the activation of CysLT1R rapidly increases intracellular Ca 2+ in ILC2s and promotes the nuclear translocation of NFAT.…”
Section: Lipid Mediators (Ltc4 Ltd4 Lte4 Ltb4 Lxa4 Pgd2 Pge2 Amentioning
confidence: 98%
“…In addition, LTC4 and LTD4 have a synergistic effect on ILC2s in combination with IL‐33. It has also been recently shown that a combination of IL‐33 with LTC4 or LTD4 can induce IL‐17 expression in ILC2s . Mechanistically, the activation of CysLT1R rapidly increases intracellular Ca 2+ in ILC2s and promotes the nuclear translocation of NFAT.…”
Section: Lipid Mediators (Ltc4 Ltd4 Lte4 Ltb4 Lxa4 Pgd2 Pge2 Amentioning
confidence: 98%
“…After BAL, lungs were dissected into pieces for enzyme digestion in RPMI-1640 medium containing DNase I (0.15 mg/mL, Sigma, USA) and collagenase II (1 mg/mL, Sigma, USA) at 37 ℃ for 1 h [27,28]. The digested tissues were homogenized by vigorous shaking and passed through a 70-μm cell strainer (BD, USA).…”
Section: Preparation Of Lung Single Cell Suspensionsmentioning
confidence: 99%
“…110 Interestingly, IL-17-producing ILC2s play a pathogenic role in a mouse model of lung allergy. 111 At the molecular level, the transcription factors Bcl11b and Gfi-1 regulate the identity of ILC2s by repressing the expression of RORγt and its associated genes. Therefore, deletion of Bcl11b or Gfi-1 in ILC2s results in IL-17 production and loss of GATA3, IL-5, and IL-13 expression.…”
Section: Type 2 Immune Response Mediated By Ilc2smentioning
confidence: 99%